APLIKASI Fusarium oxysporum NON PATOGENIK (FoNP) UNTUK MENGINDUKSI KETAHANAN BIBIT LADA TERHADAP Phytophthora capsici L. - Rita Noveriza; Mesak Tombe; H. Rialdy; Dyah Manohara (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Application of Fusarium oxysporum Non Pathogenic (FoNP) in Inducing Resistance of Black Pepper Seedlings to Phytophthora capsiciPhytophthora capsici Leon is a soil borne pathogen which is known as the causal agent of Foot rot disease of black pepper (Piper nigrum L.). Induced plant resistance against pathogens is a widespread phenomenon that has been intensively investigated with respect to the underlying signaling pathway as well as to its potential use in plant protection. This study used non pathogenic Fusarium oxysporum (FoNP) For inducing resistance on black pepper cuttings against Foot rot disease at laboratory and glass house of Phytopatology Laboratory of Indonesian Spice and Medicinal Crop Research Institute-Bogor from July until December 2004. It was observed that FoNP had ability to reduce disease severity. The level of effectiveness was 84,99 percent (at Four months seedlings). The level of effectiveness of fungicide treatment was 14,49 percent. FoNP was able to colonize black pepper seedlings up to two and a half months. The lowest viabilities of P. capsici was observed on black pepper seedling treated with Organo-TRIBA. This study suggest that FoNP has potential to be used in inducing resistace of black pepper seedlings to foot rot disease, eventually will reduce severity of the disease.